Modern problems of centralized technologies of the client-server type and possibilities of their improvement on the basis of decentralization - Горбенко, Ю.І.; Єсіна, М.В.; Мялковський, Д.В.; Акользіна, О.С.; Пономарь, В.А. (Radiotekhnika, 2019)
The paper analyzes the basic principles of building decentralized technologies with the use of blockchain technology and their requirements in terms of security, as well as the analysis of the features and conditions of the use of secure blockchain technologies. Potential attacks are described and analyzed when the use of blockchain is a significant defense mechanism against them. The essence and suggestions concerning counteraction to attacks of a special kind are given.